MORBIDITY PROFILE OF ELDERLY A CROSS SECTIONAL STUDY OF URBAN AGRA - Srivastava, Kajal; Gupta, S C; Kaushal, S K; Chaturvedi, Mridul (Indian Journal of Community Health, 2010)
Research Question: What is the morbidity profile of geriatric population in urban Agra? Objectives: 1. To assess the morbidity profile of geriatric population in Urban Agra. 2. To make comparison of above findings among urban slum and elite area.Settings: Urban Agra. Study Subject: 500 people aged 60 years and above. Statistical Analysis : Percentages, chi- square and z test. Results : Morbidity load was found to be increased with increasing age. 89.2% population of elderly were having morbidities in urban areas. Most common cause of morbidity observed was anaemia (‘26.20%) followed by cataract (24.4%,), hypertension and arthritis both as 22.2%. System wise musculoskeletal problems were most common (3 7.2%) and problems of nervous system were least (1.8%).